2012
DOI: 10.1002/bio.2375
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence quenching method for the determination of carbazochrome sodium sulfonate with aromatic amino acids

Abstract: In Britton-Robinson (BR) buffer medium (pH 3.3), carbazochrome sodium sulfonate (CSS) can react with some aromatic amino acids such as tryptophan (Trp), tyrosine (Tyr) and phenylalanine (Phe) to form a 1:1 complex by electrostatic attraction, aromatic stacking interaction and Van der Waals' force, resulting in fluorescence quenching of these amino acids. Maximum quenching wavelengths were located at 352 nm (CSS-Trp system), 303 nm (CSS-Tyr system) and 284 nm (CSS-Phe system), respectively. The fluorescence que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In order to determine the π–π stacking between PEG-PTyr and mRNA in the micelles, we investigated the fluorescence quenching of Tyr moieties in the polymer. Tyr groups have intrinsic fluorescence (λex ~280 nm, λem ~350 nm), and π–π stacking can quench the fluorescence by electron transfer [ 33 , 34 ]. Thus, we investigated the change of fluorescence signal from the Tyr groups of PEG-PGTyr polymers after forming micelles with mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the π–π stacking between PEG-PTyr and mRNA in the micelles, we investigated the fluorescence quenching of Tyr moieties in the polymer. Tyr groups have intrinsic fluorescence (λex ~280 nm, λem ~350 nm), and π–π stacking can quench the fluorescence by electron transfer [ 33 , 34 ]. Thus, we investigated the change of fluorescence signal from the Tyr groups of PEG-PGTyr polymers after forming micelles with mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…At shorter wavelengths, specifically 278 and 262 nm, Tyr and Phe are also excited. 19 It has also been shown that Tyr fluorescence overlaps with Trp fluorescence at the excitation wavelength of 275 nm. 20 Furthermore, the excitation wavelength of NPX is located around 270 nm 21 , 22 and it is clear that the fluorescence of NPX alone is too strong at shorter wavelengths.…”
Section: Methodsmentioning
confidence: 98%
“…The BSA concentration is 5.0 μM for all samples. At shorter wavelengths, specifically 278 and 262 nm, Tyr and Phe are also excited . It has also been shown that Tyr fluorescence overlaps with Trp fluorescence at the excitation wavelength of 275 nm .…”
Section: Methodsmentioning
confidence: 99%
“…As an aromatic amino acid, L-tyrosine produces endogenous fluorescence. Furthermore, L-tyrosine fluorescence quenching has previously been used in quantitative analysis [25,26].…”
mentioning
confidence: 99%